2008
DOI: 10.1002/lapl.200810072
|View full text |Cite
|
Sign up to set email alerts
|

Photothermal and accompanied phenomena of selective nanophotothermolysis with gold nanoparticles and laser pulses

Abstract: Abstract:In medical applications of laser and nanotechnology to diagnosis and treat cancer or microorganisms, understanding of lased-induced photothermal (PT) and accompanied phenomena around nanoparticles are crucial for optimization and bringing this promising technology to bedside. We analyzed the main PT-based effects in and around gold nanoparticles under action of short (nano-, pico-, and femtosecond) laser pulses with focus on photoacoustic effects due to the thermal expansion of nanoparticles and liqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
174
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(176 citation statements)
references
References 65 publications
1
174
0
1
Order By: Relevance
“…Previous work studying the effect of pulsed laser on nanoparticles showed that exposure to irradiation resulted in fragmentation of particles and the generation of new extinction peaks associated with the new population [161,169,[171][172][173]. In this work, particles with diameters ranging from 20 to 50 nm with SPRs ranging from 550 to 750 nm were subjected to NIR pulsed light for 10 min at two different powers (350 and 700 J) [170].…”
Section: The Influence Of Laser Mode and Powermentioning
confidence: 98%
See 1 more Smart Citation
“…Previous work studying the effect of pulsed laser on nanoparticles showed that exposure to irradiation resulted in fragmentation of particles and the generation of new extinction peaks associated with the new population [161,169,[171][172][173]. In this work, particles with diameters ranging from 20 to 50 nm with SPRs ranging from 550 to 750 nm were subjected to NIR pulsed light for 10 min at two different powers (350 and 700 J) [170].…”
Section: The Influence Of Laser Mode and Powermentioning
confidence: 98%
“…Another parameter involved in heat generation is the power of the operating laser as well as whether the laser is run in continuous wave (CW) or pulsed wave (PW) mode when interacting with nanoparticles [150,[159][160][161][162][163]. While there is still some debate as to which mode is best, pulsed mode is generally considered more efficient than continuous mode for heating nanoparticles in photothermal applications [150,[164][165][166][167][168].…”
Section: The Influence Of Laser Mode and Powermentioning
confidence: 99%
“…In recent years, the laser-nanostructure interaction has become of great interest due to the application of NPs in different fields, such as nano-optics and nano-electronics [1][2][3][4], laser nano-biomedicine [5][6][7][8] and catalysis [9,10]. This is due to the well-known property of metallic NPs called localized surface plasmon resonance (LSPR), in which the conduction band electrons oscillate coherently with the electric field of the incident light.…”
Section: Introductionmentioning
confidence: 99%
“…INTRODUCTION In recent years the absorption of radiation energy by NPs, light-to-heat conversion, heat dissipation and exchange with a surrounding material (medium), and following thermal and accompanied phenomena have become increasingly important topics in nanotechnology . Many reasons exist for this interest, including the applications of the light-to-heat conversion in nanoenergy [1][2][3][4][5][6][7][8][9][10][11][12], in photothermal laser nanomedicine [13][14][15][16] and catalysis [17,18], in laser processing of NPs (laser induced transformation of NP size, shape and structure) [19][20][21][22][23][24], etc. These advances in nanotechnology are based on the efficiency of light-to-heat conversion, thermal effects and the processes induced by the laser-NP interaction [1][2][3][4][5][6][7][8][9][10][11][12].…”
mentioning
confidence: 99%